Recommendations for the use of tree models to estimate national forest biomass and assess their uncertainty - Henry, Matieu (2015)
Key message Three options are proposed to improve the accuracy of national forest biomass estimates and decrease the uncertainty related to tree model selection depending on available data and national contexts.